Green synthesis of silver nanoparticles-graphene oxide nanocomposite and its application in electrochemical sensing of tryptophan - Li, Junhua; Kuang, Daizhi; Feng, Yonglan; Zhang, Fuxing; Xu, Zhifeng; Liu, Mengqin; Wang, Deping (Biosensors & bioelectronics, 2013)
A new kind of nanocomposite based on silver nanoparticles (AgNPs)/graphene oxide (GO) was conveniently achieved through a green and low-cost synthesis approach using glucose as a reducing and stabilizing agent, and the synthetic procedure can be easily used for the construction of a disposable electrochemical sensor on glassy carbon electrode (GCE). The nanocomposite was detailedly characterized by scanning electron microscopy (SEM), transmission electron microscopy (TEM), energy dispersive X-ray spectroscopy (EDX), Fourier transform infrared spectroscopy (FTIR) and electrochemical impedance spectroscopy (EIS). The experimental results demonstrated that the nanocomposite possessed the specific features of both silver nanoparticles and graphene, and the intrinsic high specific area and the fast electron transfer rate ascribed to the nanohybrid structure could improve its electrocatalytic performance greatly. Cyclic voltammetry (CV) and differential pulse voltammetry (DPV) were employed to evaluate the electrochemical properties of AgNPs/GO/GCE towards tryptophan, and the AgNPs/GO film exhibited a distinctly higher activity for the electro-oxidation of tryptophan than GO film with tenfold enhancement of peak current. The oxidation mechanism and the kinetic parameters were investigated, and analysis operation conditions were optimized. Under the selected experimental conditions, the oxidation peak currents were proportional to tryptophan concentrations over the range of 0.01 μM to 50.0 μM and 50.0 μM to 800.0 μM, respectively. The detection limit was 2.0 nM (S/N=3). Moreover, the proposed method is free of interference from tyrosine and other coexisting species. The resulting sensor displays excellent repeatability and long-term stability; finally it was successfully applied to detect tryptophan in real samples with good recoveries, ranging from 99.0% to 103.0%.